Somatic intronic TP53 c.375+5G mutations are a recurrent but under‐recognized mode of TP53 inactivation - M Herman Chui; Ciyu Yang; Nikita Mehta; Vikas Rai; Ahmet Zehir; Amir Momeni Boroujeni; Marc Ladanyi; Diana Mandelker (Wiley, 2022)
Abstract TP53 is one of the most ubiquitously altered genes in human cancer. The biological impact of rare variants, particularly those located within noncoding regions, remains poorly understood. From interrogation of clinical massively parallel sequencing data from over 55,000 tumors, which included 23,330 tumors with known TP53 mutations, TP53 intron 4 nucleotide substitutions at position c.375+5G were identified in 45 tumors (0.2% of TP53‐mutated cancers), comprising cancers of different organ sites. Loss‐of‐heterozygosity or a second‐hit somatic TP53 mutation was observed in 34 of 40 (85%) informative cases. RT‐PCR analysis showed the c.375+5G>T variant to be associated with aberrantly spliced TP53 mRNA transcripts with concomitant loss of the normal transcript. Immunohistochemical staining for p53 was performed on a representative subset of tumors with TP53 c.375+5G variants (n = 14), all of which showed loss of protein expression (100%; n = 13 complete loss, n = 1 subclonal loss). Our data are consistent with classification of TP53 c.375+5G variants as deleterious intronic mutations that interfere with proper mRNA splicing, ultimately resulting in loss of expression of functional p53 protein. The clinical scenario of a tumor with loss of p53 immunohistochemical staining, yet lacking a detectable TP53 exonic mutation, should therefore prompt consideration of splice‐altering intronic variants.